A giant osteochondroma in a boy with multiple exostoses - Kirovski, I; Gucev, Z; Tasic, V; Pop Jordanova, Nada (Macedonian Academy of Sciences and Arts, 2011)
Hereditary multiple exostoses (HME) is an inherited autosomal dominant disorder characterised by the presence of multiple exostoses, in fact benign cartilaginous tumors (enchondromata on the long bones). A six-year-old boy was found to have multiple osteochondromas on the legs, arms and ribs. Unusually, one of the osteochondromas on the right arm was huge (5 x 6 cm) and painful. X ray confirmed the benign nature of the osteochondromas. The family history was uneventful as well as the pregnancy and delivery. His intelligence is normal, and ultrasound did not detect any anomalies of the heart or kidneys. The occurrence of a large osteochondroma in a young boy is rare. In spite of its size and growth the lesion is so far benign. Frequent follow-up is recommended for the timely detection of eventual malignant transformation.